ANALYSIS OF EARNINGS QUALITY IN PHARMACEUTICAL SUB-SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Ade Ismawati; Yulia Pebrianti; Keti Purnamasari (Jurnal Manajemen, 2023)
Earnings quality is the accuracy of performance data that must be reported in the company's financial statements and shows the actual financial condition, so that earnings that are open to the public can show how much the company's profits affect decisions and can be used by shareholders when evaluating company performance. This analysis has the aim of knowing whether Investment Opportunity Set, capital structure and profitability affect the quality of earnings in pharmaceutical sub-sector companies listed on the IDX for the period 2017-2022. There are 12 populations in pharmaceutical companies, obtained as many as 5 companies as samples using purposive sampling technique. The method of analysis is multiple linear regression analysis. The results prove that simultaneously 10S, capital structure, and profitability have a significant effect on earnings quality. Partially 105 affects earnings quality, capital structure affects earnings quality, and profitability has no effect on earningsquality.